Wahyu Sebagai Sumber Dakwah - abdurrahman abdurrahman (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2004)
Al-Quran becomes a special reference and also standardmeasurement for every Moslem activities. There aremany sides that must be studied from al-Quran. As themain resource of dakwah, Al-Qur'an should be known asclose as possible. The writer explains mufass ir discourseabout revelation of wahyu.